2018
DOI: 10.1002/pen.25034
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of cellulose acetate from royal palm tree agroindustrial waste

Abstract: This study provides a novel value‐added utilization of the agroindustrial waste of royal palm tree leaf sheath to produce cellulose acetate. One of the motivations of this work was the fact that Brazil is one of the largest heart of palm producers in the world. However, as a result of extraction and processing, tons of waste are generated and discharged to the environment. Such waste is rich in lignocellulosic material, which could be reused to obtain derivatives of interest and commercial value. The synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 48 publications
(63 reference statements)
1
27
0
Order By: Relevance
“…Thus, this study showed that the resulting CA was soluble in acetone and chloroform, but insoluble in water. In line with this study, a study by Battisti et al [ 58 ] also reported that CA samples with a DS between 2.08 and 2.82 showed good solubility either in acetone or chloroform at an ambient temperature (25 °C), while the CA samples with a DS between 2.2 and 2.7 were soluble in acetone. DS values between 2.2 and 2.7 and above 2.8 belonged to cellulose diacetate and triacetate, respectively.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Thus, this study showed that the resulting CA was soluble in acetone and chloroform, but insoluble in water. In line with this study, a study by Battisti et al [ 58 ] also reported that CA samples with a DS between 2.08 and 2.82 showed good solubility either in acetone or chloroform at an ambient temperature (25 °C), while the CA samples with a DS between 2.2 and 2.7 were soluble in acetone. DS values between 2.2 and 2.7 and above 2.8 belonged to cellulose diacetate and triacetate, respectively.…”
Section: Resultssupporting
confidence: 85%
“…Confirmation of the successful acetylation process of BC to CA was identified by the appearance of new peaks in the CA samples, namely 1718–1738 cm −1 , 1369–1372 cm −1, and 1222–1232 cm −1 , which were related to the C=O stretching of carbonyl esters, the C–H bond in O−(C=O)−CH 3 and the −C−O stretching of acetyl groups, respectively. In addition, another important aspect observed in the CA spectrum was a decrease in the intensity of O–H stretching at band 3400–3200 cm −1 , when compared to BC [ 54 , 56 , 58 , 60 ]. The decrease in the intensity of hydroxyl stretching occurred because the hydroxyl groups were replaced by the acetate groups during the acetylation reaction [ 56 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,17] In recent years, due to environmental concerns, researchers have been shown profound interest with new types of filler, especially originating from a green or renewable energy source and the progress of these types of investigations are in full swing. [18] For an example, it has been found that agricultural wastes, such as various grades of rice husks, have been evaluated as filler in natural rubber (NR) based composites materials. [19,20] Ismail et al investigated the potential effect of rice husk on the blend of polypropylene and recycled acrylonitrile butadiene rubber.…”
Section: Introductionmentioning
confidence: 99%
“…Brazilian regions of the North Coast of the State of Santa Catarina cultivate huge plantations to extract canned palm hearts, with about 50 different industries in total. 17 The data provided by the Brazilian Institute of Geography and Statistics (IBGE) showed that only in 2018 in Brazil, the palm heart production corresponded to 107,923 ton, 18 demonstrating an alarming panorama for the amount of waste generated, as the palm heart corresponds to approximately 10% of the palm. Besides, the palm heart had been the main target of clandestine extraction in Brazilian forests.…”
Section: Introductionmentioning
confidence: 99%